2020
DOI: 10.1016/j.arthro.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Rotator Cuff Tear: Know When Not to Operate So You Don't Make It Worse

Abstract: Shoulder rotator cuff repair results in significantly improved outcomes compared with conservative treatment, but some repairs result in retear and, worst of all, enlarged retears (i.e., tears larger after surgery than primarily). Elevated serum total cholesterol and low-density lipoprotein levels and fatty infiltration of the infraspinatus are significantly related to symptomatic failed rotator cuff repair. Hypertension could also be a risk factor. In such cases, nonoperative treatment, reverse shoulder prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Authors demonstrated significant worst outcome when retears, a partial repair improves functional outcomes but may make the patient worse [ 29 ]. Fatty infiltration was found to be a risk factor for enlarged retear [ 52 ]; other factors were increased levels of total cholesterol and low-density lipoprotein [ 52 , 53 ]. Although we did not compare the postoperative protocol, we can assume that PCR-BT is more demanding, with longer immobilization and rehabilitation, and more immediate postoperative pain than BT.…”
Section: Discussionmentioning
confidence: 99%
“…Authors demonstrated significant worst outcome when retears, a partial repair improves functional outcomes but may make the patient worse [ 29 ]. Fatty infiltration was found to be a risk factor for enlarged retear [ 52 ]; other factors were increased levels of total cholesterol and low-density lipoprotein [ 52 , 53 ]. Although we did not compare the postoperative protocol, we can assume that PCR-BT is more demanding, with longer immobilization and rehabilitation, and more immediate postoperative pain than BT.…”
Section: Discussionmentioning
confidence: 99%